2017
DOI: 10.1590/abd1806-4841.20176198
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with butyrate and docosahexaenoic acid for keloid fibrogenesis: an in vitro study

Abstract: BackgroundA single, effective therapeutic regimen for keloids has not been established yet, and the development of novel therapeutic approaches is expected. Butyrate, a short-chain fatty acid, and docosahexaenoic acid (DHA), a ω-3 polyunsaturated fatty acid, play multiple anti-inflammatory and anticancer roles via their respective mechanisms of action.ObjectiveIn this study, we evaluated the antifibrogenic effects of their single and combined use on keloid fibroblasts.MethodsKeloid fibroblasts were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…This hypothesis is in agreement with the observations that, in vitro treatment of keloids fibroblasts with DHA (0–100 μM) reduced α-smooth muscle actin, type III collagen and TGF-β1 receptor expressions. Once again, these effects seem to be related to PPAR-γ signaling 49 .…”
Section: Discussionmentioning
confidence: 87%
“…This hypothesis is in agreement with the observations that, in vitro treatment of keloids fibroblasts with DHA (0–100 μM) reduced α-smooth muscle actin, type III collagen and TGF-β1 receptor expressions. Once again, these effects seem to be related to PPAR-γ signaling 49 .…”
Section: Discussionmentioning
confidence: 87%
“…85 These imbalances may directly influence keloid growth: when KFs are treated with DHA, their fibrogenic activity is decreased, as shown by lower expression of α-SMA, type III collagen, and the receptor for TGF-β1. 86 In addition, when KFs are treated with fish oil that is rich in omega-3 fatty acids, their proliferation is inhibited. 87 Notably, Kotronoulas et al showed recently that acellular fish skin, which has become a dermal substitute that promotes wound healing and reduces scarring, contains more polyunsaturated fatty acids than human cadaver skin.…”
Section: Omega-3 Fatty Acids In Fish Oil May Reduce Fibrosis By Altmentioning
confidence: 99%
“…The occurrence of apoptosis in BMDMs was evaluated using DAPI staining: 14 24 h after US irradiation, the cells were fixed with 4% PFA for 30 min and stained with DAPI for 5 min. As positive control, BMDMs were cultured in serum-depleted medium for 24 h to induce apoptosis.…”
Section: Methodsmentioning
confidence: 99%